Academic Senate Minutes 2003-03-20 - Academic Senate:::::::::
Agenda modified and approved. Minutes approved. Report of Chair of the Faculty. Report of President. First reading of Endorsement of Resolution from the Statewide Academic Senate - Student Fees in the CSU: Mitigating Their Effects. Introduction of new Chair-Elect and announcement of results of Spring 2003 Senate election. Report from Vice President of Administration and Finance regarding The State Auditor's report on CMS and SSU. Reports from Provost, Chair-Elect, Statewide Senator, Associated Students President, APC Chair. Resolution Against Unilateral U. S. Military Action in Iraq amended and approved.